2016
DOI: 10.11609/jott.3105.8.13.9595-9596
|View full text |Cite
|
Sign up to set email alerts
|

Parasitization of a huntsman spider (Arachnida: Araneae: Sparassidae: Heteropoda venatoria) by a mermithid nematode (Nematoda: Mermithidae)

Abstract: The emergence of a mermithid worm from a huntsman spider Heteropoda venatoria was witnessed at Buxa Tiger Reserve, West Bengal.  It appears to be a first record of the spider family Sparassidae serving as a host for a member of the family Mermithidae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The species Hersilia savignyi was the only member of the family Hersilidae noted with 12 individuals from the study site and reported earlier from Goa (Pandit and Pai, 2017), Andhra Pradesh (Pravalikha et al, 2014), Madhya Pradesh (Gajbe, 1992), Gujarat (Prajapati et al, 2018) and Kerala (Smitha et al, 2020). Similarly, Heteropoda venatoria was the only member of the family Sparassidae with 16 individuals and reported from Maharashtra (More and Sawant, 2013), West Bengal (Ranade and Prakash, 2016), Assam (Chetia and Kalita et al, 2012) and Kerala (Smitha et al, 2020). The species Clubiona drassodes from Cluboinidae family was reported with 9 individuals from the study site.…”
Section: Resultsmentioning
confidence: 89%
“…The species Hersilia savignyi was the only member of the family Hersilidae noted with 12 individuals from the study site and reported earlier from Goa (Pandit and Pai, 2017), Andhra Pradesh (Pravalikha et al, 2014), Madhya Pradesh (Gajbe, 1992), Gujarat (Prajapati et al, 2018) and Kerala (Smitha et al, 2020). Similarly, Heteropoda venatoria was the only member of the family Sparassidae with 16 individuals and reported from Maharashtra (More and Sawant, 2013), West Bengal (Ranade and Prakash, 2016), Assam (Chetia and Kalita et al, 2012) and Kerala (Smitha et al, 2020). The species Clubiona drassodes from Cluboinidae family was reported with 9 individuals from the study site.…”
Section: Resultsmentioning
confidence: 89%
“…Distribution map of mermithids parasiting in spiders throughout the whole area of Asia. All seven records (blue circles) from Asia are taken from the following literature: Okochi (1969); Matsuda (1999); Iida and Hasegawa (2003); Zamani (2014); Ranade and Prakash (2016). Our finding is marked by red coloured circle (for locality description see Material and Methods).…”
Section: Methodsmentioning
confidence: 99%
“…In eight out of nine cases of parasitized Pardosa paludicola, hosts were found dead during or after mermithid emergence. Because spiders were checked twice a day, it is possible that infected spiders died similarly as in most other cases, for example Pardosa glacialis died 30-60 minutes before a mermithid emerged [ 13 ], Pardosa pseudoannulata was usually dead at the time of nematode emergence [ 35 ], Caerostris sumatrana Strand, 1915 died immediately [ 6 ] and Heteropoda venatoria (Linnaeus, 1767) within an hour after parasitoid emergence [ 37 ]. It was a huge surprise that one female of P. paludicola lived for seven weeks after the emergence of the parasitoids.…”
Section: Molecular Datamentioning
confidence: 99%